En bro mellan teori och praktik – lärarstudenters lärandeerfarenheter av kommunicerande klassrum under verksamhetsförlagd utbildning utomlands - Nyman, Rimma; Skodras, Christina; Frisk, Susanne (Educare, 2025)
This study investigates Swedish pre-service teachers’ experiences during their practicum which is essential for their future careers. In response to recent policy changes emphasizing stronger collaboration between universities and practicum schools, and a push for higher education quality, this research addresses a gap in understanding how research-based teaching models are perceived during practicum experiences abroad. Specifically, this study explores teacher students’ experiences of high-quality mathematics instruction based on the Context for Learning (CL) teaching model. The research question guiding this study is: What aspects of CL are emphasized in primary teacher students’ perspectives on mathematics teaching following a practicum period abroad? Over three years, 12 teacher students participated in a mixed-methods study, completing part of their third practicum in schools implementing the CL model in the United States. Data were collected through classroom observations, surveys and a focus group interview. Findings reveal a strong alignment of CL principles and the teacher students’ learning experiences during their practicum. Additionally, the study underscores a perceived link between university coursework and practical teaching, suggesting that such integration can positively influence their long-term professional development.